The courtiers : splendor and intrigue in the Georgian Court at Kensington Palace - Worsley, Lucy (Walker & Co., 2010)
n the eighteenth century, Kensington Palace was a world of skulduggery, intrigue, politicking, etiquette, wigs, and beauty spots, where fans whistled open like switchblades and unusual people were kept as curiosities. Lucy Worsley<U+2019>s The Courtiers charts the trajectory of the fantastically quarrelsome Hanovers and the last great gasp of British court life. Structured around the paintings of courtiers and servants that line the walls of the King<U+2019>s Staircase of Kensington Palace<U+2014>paintings you can see at the palace today<U+2014>The Courtiers goes behind closed doors to meet a pushy young painter, a maid of honor with a secret marriage, a vice chamberlain with many vices, a bedchamber woman with a violent husband, two aging royal mistresses, and many more. The result is an indelible portrait of court life leading up to the famous reign of George III, and a feast for both Anglophiles and lovers of history and royalty--Publisher description.